Auditory Distraction in Short-term Memory: Stable Effects of Semantic Mismatches on Serial Recall. Issue 3 (3rd July 2019) - Röer, Jan Philipp; Buchner, Axel; Bell, Raoul
ABSTRACT: Recently, it was demonstrated that heard sentences containing semantically unexpected words disrupt visual-verbal serial recall more than sentences containing semantically expected words. This semantic mismatch effect did not become smaller over the course of the experiment, contrary to what has been observed with other semantic effects. This surprising finding was critically examined in the present study. In Experiment 1, unspecific habituation was investigated using a classical design and a larger number of trials compared to the original study. In Experiment 2, unspecific and specific habituation were investigated by presenting sixteen different distractor sentences in one condition and the same sentences sixteen times in the other condition. In both experiments, there was no evidence of habituation of the semantic mismatch effect. In Experiment 2, overall performance was significantly better with repeated distractor sentences as compared to different sentences, but the semantic mismatch effect remained unchanged. The disruptive effect of semantic mismatches on serial recall seems to be relatively resistant to habituation, suggesting a stable mechanism that allows to detect, and to react to, potentially meaningful information in the unattended channel.